Water security and its impact on agricultural development in Iraq for the period 2004-2022 (Entrepreneurship Journal for Finance and Business, 2025)
Through this research, the aim is to answer a number of questions that accompany the research problem of defining the concept of water security, as well as to show the extent of the effects of water security on sustainable agricultural development in Iraq for the period (2004-2022), as well as identifying water security challenges, as well as identifying alternatives to water security supplies to create sustainable agricultural development in Iraq, given the information available today.In this research, the researcher relied on the extrapolation process mainly, which is based on observing the effects of water security on sustainable agricultural development in Iraq for the period (2004-2022), and then there may be another scientific approach that we will resort to in the course of our treatment of the issue, which is the analytical method while following some standard procedures to understand the nature of the data and variables that affect the crisis.Among the most prominent results of the research: German revenues received to Iraq fluctuated from the year (2004-2022), falling below (30 billion m3) in dry years, as the results showed that agricultural activity ranked first in the process of consumption of German resources, which affects and is affected by water security, at the same time, the contribution of this activity to the pollution of surface waters due to the use of fertilizers and pesticides, and the various solid and liquid agricultural waste poses on the German Environment, and then sustainable agricultural development is significantly affected by its agricultural results, and the results surface degradation of its quality as a result of storage and causes contaminated water discharged from In general, the water crisis in Iraq was not largely a problem of shortage or scarcity of available resources, nor accelerated population growth or a deficit in financial capabilities, but it is primarily a matter of failure and imbalance in agricultural policies and misuse of the human factor of the available resources in the region with the absence of political will and seriousness in action, and we have noted through this research that food production and achieving an increase in it is dependent on Water Resources, which is a determining factor in achieving both sustainable agricultural development and water security, and that the use of Water Resources in the Iraqi agricultural sector may also To some extent, it failed to rid the state budget of import restrictions and burdens, as access to food for the Iraqi citizen is still dependent on what the West ships, especially with regard to strategic foods such as cereals, which means poor efficiency of use of Water Resources in sustainable agricultural development.The study recommended: In the absence of water security policies and strategies that regulate the management of the water sector, it is imperative to develop policies and action programs for the integrated management of water resources, as well as protecting water sources from pollution, which requires the activation of laws and legislations for water conservation and the construction of sewage and industrial water treatment plants to ensure the protection of German resources, as well as expanding the use of modern irrigation techniques such as spray and drip irrigation, redirecting water paths and distribution channels, lining irrigation channels and using pipes and automatic control gates to transport and distribute water, as well as Therefore, it is important to study and address this issue through the development of a comprehensive drought strategy in the long term in coordination with local, national and regional levels, and finally the development of national and regional plans to rationalize water uses, including the search for new resources and the study of the economics of their use and protection.